Variazione socioprosodica nell’italiano regionale di Spilamberto (MO) (Estudios de Fonética Experimental)
This paper explores the socioprosodic variability in the regional Italian of Spilamberto (Modena). It is based on an experimental study that involved 8 speakers of different age and gender who were asked to perform a reading task. The aim is to investigate how the variation of fundamental frequency, i.e. intonation, relates to sociolinguistic variation in the realisation of three statements, polar questions and exclamatives. Praat and Intsint plugin were used to transcribe and annotate the data. The results, obtained through both quantitative and qualitative analysis, show that 1) exclamatives are realised at higher frequency levels than other sentence types; 2) gender and age play a role in differentiating the intonational patterns of read statements.